Fe-doping enabled a stable vanadium oxide cathode with rapid Zn diffusion channel for aqueous zinc-ion batteries. (September 2021) - Wu, Fangfang; Wang, Youwei; Ruan, Pengchao; Niu, Xinxin; Zheng, Dong; Xu, Xilian; Gao, Xiaobin; Cai, Yanhui; Liu, Wenxian; Shi, Wenhui; Cao, Xiehong
Abstract: Vanadium-based oxides with high theoretical specific capacity and open crystal structure are promising cathodes for aqueous zinc ion batteries. However, the frustrating dissolution and structural collapse of vanadium-based oxides, especially when cycling at a low current density, lead to severe performance degradation. Here, we demonstrate doping of Fe opens up a rapid Zn 2+ diffusion channel,  and results in a stable layer-structured vanadium oxide nanobelt (FeVO) with an expanded interlayer spacing up to 10.8 Å. This enables a cathode with high structural stability, leading to an outstanding cyclic stability of 300 cycles at a low current density of 0.5 A g −1 with a high retention of 94.6%. Even cycling at 0.2 A g −1, the Fe-doped vanadium oxide still maintains a retention of 93.6% after 150 cycles. A reversible co-intercalation mechanism of Zn 2+ and H2 O is further revealed via ex - situ X-ray powder diffraction (XRD) and X-ray photoelectron spectra techniques. Such boosted electrochemical performance is attributed to the large interlayer space providing ion diffusion path and a stable layered structure. These excellent characteristics of the prepared vanadium oxide cathode show great potential for high-performance aqueous zinc ion batteries. Graphical abstract: Image 1 Highlights: The incorporation of Fe opens up a rapid Zn 2+ diffusion channel with an expanded interlayer spacing of 10.8 Å. The Fe-doping vanadium oxide nanobelt shows excellent cycling stability, especially in cycling at a low current density. The Zn 2+  (de)intercalation mechanism is confirmed by  ex - situ  X-ray powder diffraction and X-ray photoelectron spectra.